A SCANNING ELECTRON-MICROSCOPIC STUDY OF EXTERNAL ROOT RESORPTION IN REPLANTED DOG TEETH - (:unkn) unknown (ELSEVIER SCIENCE INC, 1995)
Root resorption after replantation of mature permanent dog incisors was examined by scanning electron microscopy. Three groups consisting of three extracted teeth each were kept in a saline solution for 5, 30, and 120 min before replantation, The first group was replanted with the pulp intact, The second and third groups were replanted after root canal filling by Calciobiotic Root Canal Sealer. After 90 days, the teeth were extracted and the apical root surfaces were examined, Severe inflammatory root resorption was observed in the first (intact pulp) group, For the root canal filled teeth, the degree of root resorption was observed to be much less in those kept in saline for 30 min than in those kept for 120 min.
Keywords: MATURE PERMANENT INCISORS; MONKEYS; STORAGE